2017
DOI: 10.1536/ihj.16-190
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA Damage in Leukocytes of Patients With Coronary Artery Disease by Comet Assay

Abstract: SummaryDNA damage in the peripheral blood leukocytes (PBL) of patients with coronary artery disease (CAD) was investigated using the sensitive alkaline single cell gel electrophoresis (SCGE)/comet assay.This case-control study consisted of CAD patients (n = 200; mean age, 59.04 ± 0.75 years) undergoing treatment at local hospitals and age-, sex-, and ethnicity-matched healthy controls (n = 200; mean age, 57.88 ± 0.96 years) from the general population.CAD patients had significantly (P < 0.001) increased DNA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…According to their studies, DNA damage was significantly higher in coronary artery disease patients than in the control group (p<0.001). Similarly, Bhat & Gandhi (2017) showed that DNA damage in cardiovascular patients was significantly (p<0.001) more than in the control group. They evaluated comet parameters and found that tail DNA percent was 22.45 ± 0.50 and tail moment was 89.35±3.16.…”
Section: Discussionmentioning
confidence: 91%
“…According to their studies, DNA damage was significantly higher in coronary artery disease patients than in the control group (p<0.001). Similarly, Bhat & Gandhi (2017) showed that DNA damage in cardiovascular patients was significantly (p<0.001) more than in the control group. They evaluated comet parameters and found that tail DNA percent was 22.45 ± 0.50 and tail moment was 89.35±3.16.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, the neutral single-cell gel electrophoresis method was used for detection, which mainly detected the breaking of DNA double strands, with high specificity. Compared with other parameters, and TM and TDNA had a higher correlation with the degree of DNA damage and were more sensitive and accurate [17,18]. According to the research of Chen et al [19], although many mosaic algorithms are implemented based on SIFT algorithm, radiation damage suffered by cardiovascular intervention patients is generally acute radiation damage.…”
Section: Discussionmentioning
confidence: 99%